PERKEMBANGAN JAGUNG PADA DEKADE TERAKHIR SERTA PELUANG PENGEMBANGAN KEDEPAN - SUDANA, WAYAN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 1 Februari 2005, 2012)
Maize is the one important cereal crop after rice, for the last decade domestic demand for maize was steadily increasing. This study is aimed to evaluate the development of maize production for the last decade, and the opportunity of maize production development in future. Based on CBS data, during the last decade (1990 – 2000) there was a big opportunity to develop maize production in the future, through intensification or extensification. Intensification, can be met by minimize yield gap between farm’s yield and potential yield by introducing of improve technology, and use of high yield variety. Extensification can be achieved by increasing cropping index through implementation proper cropping pattern especially on irrigated land, and in the upland condition by implementing intercropping technique. Extensification also can be done by utilizing swampy area and upland area, where are available in outer of Java island.
Keywords: maize, development, intensification and extensification